Comprehensive Polyphenolic Profile of Plantago depressa using High‐Speed Countercurrent Chromatography Off‐line with High‐Performance Liquid Chromatography–Diode Array Detector–Quadrupole Time‐of‐flight Tandem Mass Spectrometry. Issue 1 (14th November 2019) - Xu, Jinju; Tong, Chaoying; Fu, Qiachi; Guo, Keke; Shi, Shuyun; Xiao, Yecheng
Abstract : The whole plant of Plantago depressa is commonly used as traditional Chinese medicine and functional food ingredient. Total phenolic content and total flavonoid content evaluation indicated that its ethyl acetate and n ‐butanol fractions were rich in polyphenols. However, to date, the polyphenolic profile is limited because of the complex matrix. Here, polyphenols in ethyl acetate and n ‐butanol fractions of P. depressa were first separated and enriched by High‐Speed Countercurrent Chromatography (HSCCC). Then, their structures were characterized or tentatively identified by High‐Performance Liquid Chromatography (HPLC)–Diode Array Detector (DAD)–Quadrupole Time‐of‐Flight Tandem Mass Spectrometry (QTOF‐MS/MS) (HSCCC × HPLC–DAD–QTOF‐MS/MS). Because of the orthogonality of HSCCC and HPLC, 37 polyphenols were identified. Notably, 29 polyphenols were discovered from P. depressa for the first time. Finally, contents of two potential new compounds, 2‐ethoxy plantamajoside isomers (17 and 29 ), were determined as 0.27 ± 0.03 and 0.04 ± 0.01 mg/g, respectively. Results indicated that P. depressa could be used as a promising source of polyphenols for health promotion, and the developed method (HSCCC × HPLC) was efficient to explore polyphenolic profile for complex natural products.